BFT water color classification in tilapia aquaculture using computer vision - Suwandi, Bondan; Anggraeni, Sakinah Puspa; Palokoto, Toto Bachtiar; Sulistya, Budi; Sujatmiko, Wisnu; Septiawan, Reza; Taufik, Nashrullah; Rufiyanto, Arief; Ardiansyah, Arif Rahmat (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Biofloc technology (BFT) is one of the most promising aquaculture cultivation methods in the modern aquaculture era because of its high efficiency level, especially in water and fodder use. Usually, the general condition of the biofloc can be known from the color of the water. By utilizing the vision sensor, BFT color identification can be done automatically, which helps cultivators find out their BFT system’s condition. In this research, a classification was made for the watercolor of the BFT Tilapia system based on the microbial community color index (MCCI) value and the initial cultivation conditions where algae and nitrifying bacteria had not developed significantly. The color classifications of the bioflocs are clear, green, browngreen, green-brown, and deep-brown. Clear color is the new classification to indicate BFT water conditions in the initial cultivation phase. Further, two computer vision algorithm methods are introduced to classify the color of BFT system water. The first method combines the B/W algorithm and MCCI calculations, while the second algorithm uses the Manhattan distance algorithm approach. From the experiments that have been carried out, both computer vision algorithms methods for classifying biofloc colors have shown promising results.